Diet Pattern and Psychological Conditions in Adolescents During Covid-19 Isolation - Sriwiyanti; Sri Hartati (Yayasan Rumah Ilmu Professor, 2022)
Social isolation has a negative impact on eating habits and mental health. especially in adolescents. Teenagers' daily lives have changed dramatically during the COVID-19 era due to the social restrictions that have been imposed, including the closure of schools, recreation centers and sports facilities. The purpose of this study was to assess the diet carried out during isolation with psychological adolescents. A total of 206 teenagers took the online survey. Participants showed negative psychological, and healthy diet at moderate limits. Hierarchical regression analysis shows that a healthy diet has a positive psychological effect. The results of the study found that adolescent psychology in this study was below the threshold recommended by the World Health Organization as an indication of possible depressive symptoms, measures to reduce wrong dietary behavior in adolescents a priority for the community and policy makers.